LEARNING STRATEGIES AND ANXIETY ON GRAMMAR ACHIEVEMENT - Noor Rachmawaty; Setya Ariani (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2019)
Successful foreign or second language instruction involves individual learning differences as important variables observed among students. Out of many variables, learning strategies and anxiety are highlighted to be major concerns influencing grammar achievement. This paper sought to examine whether learning strategies and anxiety reported by EFL students influencing grammar scores. Strategy Inventory for Language Learning (SILL) and Foreign Language Classroom Anxiety Scale (FLCAS) questionnaires were administered to fifty-nine student samples. Path analysis was used to map the relationship model of the variables in this study. The statistical analysis revealed that the influence of learning strategies and anxiety on grammar score was 0.063 or 6.3%. This implied that 93.7% of students’ grammar score was influenced by other variables. The statistical analysis also showed that there was a negative correlation between learning strategies and grammar scores (r = -200, p<.05). Similarly, a negative correlation was also seen in anxiety and grammar score (r = -146, p<.05). The findings contribute to improve the quality of teaching grammar and provide recommendation for future studies in the area of teaching and learning grammar in the EFL context.